2011
DOI: 10.1073/pnas.1018925108
|View full text |Cite
|
Sign up to set email alerts
|

Coexpression of VEGF and angiopoietin-1 promotes angiogenesis and cardiomyocyte proliferation reduces apoptosis in porcine myocardial infarction (MI) heart

Abstract: VEGF and angiopoietin-1 (Ang1) are two major angiogenic factors being investigated for the treatment of myocardial infarction (MI). Targeting VEGF and Ang1 expression in the ischemic myocardium can increase their local therapeutic effects and reduce possible adverse effects. Adeno-associated viral vectors (AAVs) expressing cardiac-specific and hypoxia-inducible VEGF [AAV-myosin light chain-2v (MLC)VEGF] and Ang1 (AAV-MLCAng1) were coinjected (VEGF/Ang1 group) into six different sites of the porcine myocardium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
109
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 158 publications
(116 citation statements)
references
References 36 publications
6
109
0
1
Order By: Relevance
“…Increased expression of VEGF and Angiopoietin-1 has been shown to improve perfusion by inducing angiogenesis and myocardial proliferation in a porcine model of myocardial infarction. 27 In the current study, Angiopoietin-1 was more highly expressed in the VEGF-treated animals as well.…”
Section: Discussionmentioning
confidence: 63%
“…Increased expression of VEGF and Angiopoietin-1 has been shown to improve perfusion by inducing angiogenesis and myocardial proliferation in a porcine model of myocardial infarction. 27 In the current study, Angiopoietin-1 was more highly expressed in the VEGF-treated animals as well.…”
Section: Discussionmentioning
confidence: 63%
“…We also examined the expression of Vegfa because previous studies have shown that the Vegf promoter is repressed by Cited2 (34). In addition, delivery of VEGF to the injured heart has been shown to induce cardiomyocyte proliferation (35,36). As shown in Fig.…”
Section: Identification and Validation Of Predicted Target Genes Of Mmentioning
confidence: 98%
“…Ang-1 expression falls dramatically after focal cerebral ischemia, resulting in a leaky blood-brain barrier. Increases in Ang-1 levels, however, preserve vascular integrity after focal ischemia and/or VEGF administration (Thurston et al, 2000;Tao et al, 2011). The use of the aforementioned angiogenic and vascular protective factors might seem to be a promising treatment of acute ischemic stroke.…”
Section: Introductionmentioning
confidence: 99%